2015
DOI: 10.1371/journal.pone.0118700
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Morphological Changes in Endocrine Pancreas following Cola Drink Consumption in Rats

Abstract: AimWe report the effects of long-term cola beverage drinking on glucose homeostasis, endocrine pancreas function and morphology in rats.MethodsWistar rats drank: water (group W), regular cola beverage (group C, sucrose sweetened) or “light” cola beverage (group L, artificially sweetened). After 6 months, 50% of the animals in each group were euthanized and the remaining animals consumed water for the next 6 months when euthanasia was performed. Biochemical assays, insulinemia determination, estimation of insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 30 publications
(36 reference statements)
6
30
3
Order By: Relevance
“…Cola drinking induced overall changes in plasma biochemistry and in pancreatic islets morphology in agreement with previous reports [ 22 24 ]. Previously, we reported replication of most features of metabolic syndrome in our experimental model of cola drink consumption.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Cola drinking induced overall changes in plasma biochemistry and in pancreatic islets morphology in agreement with previous reports [ 22 24 ]. Previously, we reported replication of most features of metabolic syndrome in our experimental model of cola drink consumption.…”
Section: Discussionsupporting
confidence: 92%
“…In regard to our previous publications [ 24 , 25 ], different rat batches from the same breeders were used in the respective experiments at, of course, not only different seasons but different years as well. The experimental design in the present study is analogous to that reported recently in this journal [ 25 ] though different sets of animals were evaluated for respectively different purposes according to the respective topics of the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed mechanisms by which sugar-sweetened beverage intake may increase diabetes risk are predominantly related to induced insulin resistance (29) and include decrease in hepatic insulin sensitivity (30), adverse effects of increased insulin demand due to high intermittent spikes in blood glucose levels (16) and increase in inflammatory markers such as C-reactive protein (31). Another possibility is that the increased risk is mediated by increases in overweight (32).…”
Section: Discussionmentioning
confidence: 99%
“…Significant consumption of large amounts of sugar, such as sucrose, independently increases the risk of becoming overweight and obese (Stanhope, 2016). Additionally, sugar sweetened dietary intake not only elevates calories that, in turn, increase fat and weight, but also may affect glucose homeostasis and insulin sensitivity (Malik et al, 2013;Otero-Losada et al, 2015). Recent studies found that a high intake of sweetened food and beverage elevates the risk of insulin resistance, which consequently decreases hepatic insulin sensitivity and triggers the onset of type 2 diabetes (Bhupathiraju et al, 2013;Maki et al, 2015;Sakurai et al, 2014).…”
Section: Sweeteners Obesity and Diabetesmentioning
confidence: 99%